Appropriate Telemedicine Utilization in Spine Surgery: Results From a Delphi Study. Issue 8 (4th February 2022) - Iyer, Sravisht; Bovonratwet, Patawut; Samartzis, Dino; Schoenfeld, Andrew J.; An, Howard S.; Awwad, Waleed; Blumenthal, Scott L.; Cheung, Jason P.Y.; Derman, Peter B.; El-Sharkawi, Mohammad; Freedman, Brett A.; Hartl, Roger; et al.
Abstract : An expert panel of spine surgeons had consensus that video-based telemedicine could be utilized regardless of patient location, is sufficient for evaluation and indication of surgery for multiple common spine pathologies, such as lumbar stenosis, lumbar radiculopathy, as well as cervical radiculopathy, and could be appropriate for various visit types. Abstract : Study Design: Delphi expert panel consensus. Objective: To obtain expert consensus on best practices for appropriate telemedicine utilization in spine surgery. Summary of Background Data: Several studies have shown high patient satisfaction associated with telemedicine during the COVID-19 peak pandemic period as well as after easing of restrictions. As this technology will most likely continue to be employed, there is a need to define appropriate utilization. Methods: An expert panel consisting of 27 spine surgeons from various countries was assembled in February 2021. A two-round consensus-based Delphi method was used to generate consensus statements on various aspects of telemedicine (separated as video visits or audio visits) including themes, such as patient location and impact of patient diagnosis, on assessment of new patients. Topics with ≥75% agreement were categorized as having achieved a consensus. Results: The expert panel reviewed a total of 59 statements. Of these, 32 achieved consensus. The panel had consensus that video visits could be utilized regardless of patient location and that video visits are appropriate for evaluating as well as indicating for surgery multiple common spine pathologies, such as lumbar stenosis, lumbar radiculopathy, and cervical radiculopathy. Finally, the panel had consensus that video visits could be appropriate for a variety of visit types including early, midterm, longer term postoperative follow-up, follow-up for imaging review, and follow-up after an intervention (i.e., physical therapy, injection). Conclusion: Although telemedicine was initially introduced out of necessity, this technology most likely will remain due to evidence of high patient satisfaction and significant cost savings. This study was able to provide a framework for appropriate telemedicine utilization in spine surgery from a panel of experts. However, several questions remain for future research, such as whether or not an in-person consultation is necessary prior to surgery and which physical exam maneuvers are appropriate for telemedicine. Level of Evidence: 4